â€œEffect of various drying methods on quality and flavor characteristics of mint leaves (Mentha spicata L.)â€ - Kripanand, Sathiyamala; Guruguntla, Sulochanamma; korra, srinivasulu (Journal of Food and Pharmaceutical Sciences, 2015)
Mint leaves were dehydrated by hot air, shade as well as microwave drying and the respective drying time found, to lower the moisture content from (88%) to around (5%). The qualities of the dried products were assessed by determining the moisture, chlorophyll, carotenoid, polyphenols, color and volatile oil. In microwave drying, despite the less drying time, there were appreciable losses of volatile oil, chlorophyll and other components when compared to the fresh mint leaves. Results showed that Hot Air Drying (HAD) at 45Â°C followed by Micro Wave Drying (MWD) at 900 Watts possessed better quality parameters in the dried products suggesting that Hot Air Drying (HAD) was most suitable although it took more time compared to Micro Wave Drying (MWD).Â